Ethical relationality, TribalCrit, and autobiographical narrative inquiry: Imagining coming alongside Indigenous children - Cardinal, Trudy; Stavrou, Stavros; Murphy, M. Shaun; Huber, Janice (Frontiers in Education, 2023)
Creating this chapter brought us together as a diverse group of scholars to think deeply about a process of reflection in teacher education that centers on ethical relationality. To show our coming alongside adult learners attentive to reflection that centers ethical relationality, we inquire into both the Assessment as Pimosayta courses that Murphy, Cardinal, and Huber teach and into Stavrou's experiences teaching and enacting assessment in his practice. The body of our chapter is structured by the five design elements foregrounded by Stavrou and Murphy's recent bringing of critical race theory and anti-racist education to narrative inquiry: beginning with experience; carrying theoretical frameworks into an inquiry; negotiating theoretical frameworks with participants; using narrative threads to show the complexity of experience; ending in experience. Centering ethical relationality as we come alongside pre- and in-service teachers as they imagine coming alongside Indigenous children, youth, families, and communities lifts the long-termness of our work, including that this long-termness entails interactions and responsibilities with other humans and more-than-human beings.